Shear bond strength of orthodontic fluoride releasing color change adhesive: an in vitro study (Research, Society and Development, 2022)
Objective: To assess, in vitro, the shear bond strength and the adhesive remnant index (ARI) of brackets bonded with TransbondTM Plus Color Change adhesive. Design: Laboratory study of shear bond strength. Setting: Orthodontic brackets were bonded on bovine teeth and submitted to a mechanical shear test. Methods: Forty-five bovine teeth were randomly divided into three groups for orthodontic bracket bonding with Transbond™ XT adhesive light cured for 10 seconds (group XT10) and TransbondTM Plus Color Change light cured for 5 seconds (CC05 group) and 10 seconds (CC10 group). The specimens were submitted to a mechanical shear test and the enamel was examined under the stereoscopic microscope to determine the ARI. Results: There was no significant difference in shear strength between the groups, considering adhesive type (p = 0.137) and polymerization time (p = 0.958). According to the ARI scale, 86.7 % of the teeth in CC10 and CC05 groups presented more than half of the adhesive left on them, while in XT10 group 73.3 % of the teeth presented less than half of the adhesive left on them, and this difference was significant. Conclusion: The use of the TransbondTM Plus Color Change adhesive resulted in a non-significant reduction in the shear bond strength and in a greater adhesive/bracket interface failure when compared to TransbondTM XT.